Does it Work?: Applying English Translation Shift to Achieve Students Ability - Alfons Napoleon Arsai; Almendita Flora Wendelmood Arsai (Journal of English Culture, Language, Literature and Education, 2024)
This study investigates the translation abilities of English Education students specifically the 2022 cohort at the English Education Department Faculty of Teacher Training and Education University of Papua Conducted in March 2024 this research adopts a quantitative method utilizing a translation shift approach to analyze the collected data The study s sample consisted of 20 purposively selected students from the 2022 batch Arikunto 1993 A translation test was employed as the primary data collection instrument focusing on simple phrases and sentences The collected quantitative data were analyzed to evaluate students translation skills and determine the frequency of applied translation shifts The findings reveal that students predominantly utilized translation shifts in their translations with the most frequent being structure shifts and unit shifts These shifts highlight the students preference for adapting grammatical structures and linguistic units to achieve equivalence between the source and target languages Moreover out of six recognized types of translation shifts the students successfully demonstrated competence in four reflecting their ability to handle a range of translation challenges based on the provided test items < p>